2014
DOI: 10.1515/jpem-2014-0068
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum 25-hydroxyvitamin D with race/ethnicity and constitutive skin color in urban schoolchildren

Abstract: The objective of this study was to determine the extent to which constitutive skin color explains racial/ethnic differences in serum 25-hydroxyvitamin D (25OHD) concentrations in urban schoolchildren. Analysis of covariance (ANCOVA) was used to determine associations of 25OHD with parent-reported race/ethnicity and constitutive skin color as measured by reflectance colorimeter [individual typology angle (ITA°; higher value corresponds to lighter skin)] in 307 Greater Boston schoolchildren aged 9–15 during Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…It is known that vitamin D deficiency occurs in up to 20%-70% of children, regardless of age, sex, socioeconomic status, and dietary supplementation. The main variation in its occurrence may easily be explained by race or ethnicity and seasonal influences (ie, it is more commonly observed among darker individuals owing to differing skin pigmentation and in the winter because of reduced sun exposure) [41][42][43][44] Our analysis indicates that vitamin D status depends on more than a GFD and supplementation, considering that two-thirds of patients who were prescribed supplements to correct vitamin D deficiency still did not achieve normal levels. Therefore, it seems that vitamin D deficiency may not be directly linked to CD, but merely represents its frequency in the general population.…”
Section: Discussionmentioning
confidence: 90%
“…It is known that vitamin D deficiency occurs in up to 20%-70% of children, regardless of age, sex, socioeconomic status, and dietary supplementation. The main variation in its occurrence may easily be explained by race or ethnicity and seasonal influences (ie, it is more commonly observed among darker individuals owing to differing skin pigmentation and in the winter because of reduced sun exposure) [41][42][43][44] Our analysis indicates that vitamin D status depends on more than a GFD and supplementation, considering that two-thirds of patients who were prescribed supplements to correct vitamin D deficiency still did not achieve normal levels. Therefore, it seems that vitamin D deficiency may not be directly linked to CD, but merely represents its frequency in the general population.…”
Section: Discussionmentioning
confidence: 90%
“…Another potential limitation is lack of data on degree of skin pigmentation. However, two recent studies of skin pigmentation and 25(OH)D levels among several racial/ethnic groups found that measured constitutive skin color did not improve prediction of 25(OH)D concentrations when included in a model that had terms for race/ethnicity [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melanin levels were inversely correlated with the increase in vitamin D levels. In a study of racially diverse children in Boston, most of the variability in 25(OH)D was correlated with constitutive skin color [38].…”
Section: Vitamin D and Skin Of Colormentioning
confidence: 99%